Role of Chemokines and Chemokine Receptors in Shaping the Effector Phase of the Antitumor Immune Response - Franciszkiewicz, Katarzyna; Boissonnas, Alexandre; Boutet, Marie; Combadière, Christophe; Mami-Chouaib, Fathia (Cancer research (Chicago, Ill.), 2012)
Immune system–mediated eradication of neoplastic cells requires induction of a strong long-lasting antitumor T-cell response. However, generation of tumor-specific effector T cells does not necessarily result in tumor clearance. CTL must first be able to migrate to the tumor site, infiltrate the tumor tissue, and interact with the target to finally trigger effector functions indispensable for tumor destruction. Chemokines are involved in circulation, homing, retention, and activation of immunocompetent cells. Although some of them are known to contribute to tumor growth and metastasis, others are responsible for changes in the tumor microenvironment that lead to extensive infiltration of lymphocytes, resulting in tumor eradication. Given their chemoattractive and activating properties, a role for chemokines in the development of the effector phase of the antitumor immune response has been suggested. Here, we emphasize the role of the chemokine–chemokine receptor network at multiple levels of the T-cell–mediated antitumor immune response. The identification of chemokine-dependent molecular mechanisms implicated in tumor-specific CTL trafficking, retention, and regulation of their in situ effector functions may offer new perspectives for development of innovative immunotherapeutic approaches to cancer treatment. Cancer Res; 72(24); 6325–32. ©2012 AACR.